The effect of teacher training and community literacy programming on teacher and student outcomes - Chimbutane, Feliciano; Karachiwalla, Naureen; Herrera-Almanza, Catalina; Leight, Jessica; Lauchande, Carlos (Elsevier, 2026)
Motivated by extremely low levels of basic reading skills in sub-Saharan Africa, we experimentally evaluate two interventions designed to enhance students’ early-grade literacy performance in rural Mozambique: a relatively light-touch, scalable teacher training in early-grade literacy including the provision of pedagogical materials, and teacher training and materials in conjunction with community-level reading camps. Using data from 1,596 third graders in 160 rural public primary schools, we find no evidence that either intervention improved teachers’ pedagogical knowledge or practices or student or teacher attendance following two years of implementation. There are some weak positive effects on student reading as measured by a literacy assessment, primarily observed in a shift away from scores of zero, and these effects are consistent across arms. Our findings are aligned with the growing consensus that more intensive school- and/or community-based interventions are required to meaningfully improve learning.